Esensi Viral ‘Ojo Dibandingke’ dalam Spektrum Pendidikan Islam - Salis Irvan Fuadi; Robingun Suyud El Syam (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The research aims to reveal the viral essence of 'Ojo Dibandingke' in the spectrum of Islamic education. The article is a literary research with a phenomenological approach and qualitative analysis. Based on the research, it was concluded: if you compare yourself in worldly matters, you have to look at it first. If this attitude makes us enthusiastic to improve our self-quality then it is permissible, even recommended. Like comparing yourself with the enthusiasm of learning others. Conversely, if such things actually make us less grateful or arouse desire, then it is not permissible. Meanwhile, in terms of comparing ourselves in matters of the hereafter, it is absolutely permissible because it can stimulate our spirit of worship. In the spectrum of Islamic education, comparing is a disgraceful character that must be avoided. Research recommends that the viral essence of 'Ojo Dibandingke' in the spectrum of Islamic education is more specifically needed for the depth of the material.